HUBUNGAN PELAKSANAAN FUNGSI MANAJEMEN KEPALA RUANGAN DENGAN PENERAPAN PATIENT SAFETY DI RUANG PERAWATAN RSUD KOTA MAKASSAR: Correlation Between The Implementation of Management Function of Head Nurse and Patient Safety in Treatment Ward Makassar City Hospital - La Masahuddin; Rini Rachmawaty; Burhanuddin Bahar (Jurnal Ilmiah Keperawatan (Scientific Journal of Nursing), 2020)
Introduction: The "Patient safety" movement has become a spirit in hospital nursing services throughout the world, not only hospitals in developed countries that implement patient safety to ensure the quality of health and nursing services, but also hospitals in developing countries, such as Indonesia.Objective: The relationship between the implementation of the functions of planning, organizing, directing and controlling the head of the room with the application of patient safety by nurses in Makassar City Hospital.Method: this research is a quantitative research with cross sectional approach. The study was conducted in the inpatient room of the Makassar City General Hospital of 63 nurses implementing it (simple random sampling). The method of collecting data using a checklist questionnaire by distributing questionnaires, the implementation of head room management functions with the application of patient safety using the Spearman 's rho correlation test.Results: The results showed that there was a significant relationship between the function of head room management with the application of patient safety by nurses in Makassar City Hospital with a value of p = 0.009 and a Spearman's rho correlation value of 0.327, in organizing a value of p = 0.042 and a spearman correlation value of 0.257, at controlling for p value = 0,023 and spearman correlation value 0,285. There is no significant relationship between the implementation of the head room planning management function obtained p value = 0.095 and Spearman's correlation value rho 0.212, the head room directional function with the application of patient safety with a value of p = 0.530 and the spearman correlation value of 0.081. Discussion : of the results showed that the more the better the implementation of the head room management function, the better the implementation of patient safety by nurses in Makassar City HospitalConclusion: The head of the room needs to always improve the planning and direction function in an effort to civilize the application of patient safety so that there will be a good quality of patient safety in the Makassar City Hospital service environment.Keywords: Head of Management Function room, patient safety, nurses